Pertumbuhan dan Hasil Tanaman Ubi Alabio (Dioscorea alata L.) yang Diberikan Pupuk Organik Cair (POC) dari Kotoran Kambing - Diana Sari, Desty; Sulaiman, Firdaus; Irmawati, Irmawati; Rethanasya, Dea; Sonnia, Riri Rizki; Damayanti, Siti Hanny; Pamungkas, Ridho; Miralisa, Ayu Tika (Seminar Nasional Lahan Suboptimal, 2024)
Sari, D. D., Sulaiman, F., Irmawati, I., Rethanasya, D., Sonnia, R. R., Damayanti, S. H., Pamungkas, R., Miralisa, A. T. (2024). Growth and yield of cassava alabio plants (Dioscorea alata L.) given liquid organic fertilizer (POC) from goat manure. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 235–243). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Ubi alabio (Dioscorea alata L.) is a type of yam plant that is widely cultivated in lebak swamplands and is classified as a shrub and grows vines with a length of 3-10 metres. Problems that are still faced by many farmers, namely the presence of pest attacks by caterpillars, beetles and aphids so that good tillage and plant maintenance are needed. This study aimed to determine the optimal growth results of alabio sweet potatoes with the use of Liquid Organic Fertiliser from goat manure. The method used is Randomised Group Design (RAK), which is a repetition method. The results of this study that the goat manure POC factor consists of 5 levels with 5 replicates and each replicate consists of 5 plants, so that the number of plants observed is 125 plants. In stem length, goat manure POC affects plant growth, stem length is increasingly influential at week 4 after planting, but at week 16 the plant has no real effect. In the analysis of stem height observations, goat manure POC had no significant effect on the growth of the main stem height with the highest number of 546 cm at 16 weeks after planting. For the number of leaves, POC has no significant effect on the observation variable time at the highest result is at 291.8 at 16 weeks after planting. In the observation of the number of branches, goat manure POC had no significant effect on the number of branches, for the highest results obtained at 6.44 at 16 weeks after planting. This study concluded that the use of POC from goat manure can be a good alternative to increase agricultural yields, although it is necessary to choose the right concentration to achieve optimal results.